Performance of an optical encoder based on a nondiffractive beam implemented with a specific photodetection integrated circuit and a diffractive optical element - Perez Quintian, Luis Fernando (2015)
In this paper, we study the incremental signal produced by an optical encoder based on a nondiffractive beam (NDB). The NDB is generated by means of a diffractive optical element (DOE). The detection system is composed by an application specific integrated circuit (ASIC) sensor. The sensor consists of an array of eight concentric annular photodiodes, each one provided with a programmable gain amplifier. In this way, the system is able to synthesize a nonuniform detectivity. The contrast, amplitude, and harmonic content of the sinusoidal output signal are analyzed. The influence of the cross talk among the annular photodiodes is placed in evidence through the dependence of the signal contrast on the wavelength.